Study of the impact of climate change on economic growth in North African and Sahel countries - Brika, Said Khalfa; Bengana, Ismail; Mili, Khaled (International Journal of Innovative Research and Scientific Studies, 2025)
This research paper aims to investigate the impact of climate change on economic growth, represented by GDP per capita, for a group of North African and Sahel countries during the period 1965-2020. As part of the Autoregressive Distributed Lag (ARDL) model approach, the study examined this relationship both in the short and long term. The short term utilized static analysis, while the long term employed co-integration analysis. These two analyses revealed a negative effect of temperature rise in the short term and a positive effect of precipitation in the long term. This necessitates that the governments of the sample countries respond appropriately to adapt to environmental phenomena that are harmful to their economies.